PepFect14 mediates the delivery of mRNA into human primary keratinocytes and in vivo - Periyasamy, Kapilraj; Maloverjan, Maria; Biswas, Abhijit; Remm, Anu; Pook, Martin; Rebane, Ana; Pooga, Margus (Frontiers in Pharmacology, 2023)
mRNA-based vaccines and candidate therapeutics have great potential in various medical fields. For the delivery of mRNA into target cells and tissues, lipid formulations are often employed. However, this approach could cause the activation of immune responses, making it unsuitable for the treatment of inflammatory conditions. Therefore, alternative delivery systems are highly demanded. In this study, we evaluated the transport efficiency and characteristics of cell-penetrating peptide PepFect14 (PF14) and mRNA nanoparticles in the presence of different additives. Our results show that all PF14-mRNA formulations entered cultured cells, while calcium chloride enhanced the transport and production of the encoded protein in HeLa and HaCaT cell lines, and polysorbate 80 did so in primary human keratinocytes. All formulations had similar physical properties and did not remarkably affect cell viability. By selectively blocking endocytosis pathways, we show that PF14-mRNA nanoparticles primarily entered HeLa cells via macropinocytosis and HaCaT cells via both macropinocytosis and clathrin-mediated endocytosis, while none of the blockers significantly affected the delivery into primary keratinocytes. Finally, subcutaneous injection of PF14-mRNA nanoparticles before inducing mouse irritant contact dermatitis resulted in the expression of a reporter protein without provoking harmful immune responses in the skin. Together, our findings suggest that PF14-mRNA nanoparticles have the potential for developing mRNA-based therapeutics for treating inflammatory skin conditions.